PENERAPAN MODEL KOOPERATIF TIPE CIRC UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN MEMBACA PEMAHAMAN PADA SISWA KELAS VIII SMP PURNAMA 3 KOTA JAMBI - Supriyati Supriyati (Jurnal Ilmiah Dikdaya, 2018)
The lack of students ability in understanding reading texts show that the students are not able to understand reading comprension learning. This is why some efforts are made to increase the students learning process and by using CIRC Cooperative Model. This research is intended to identify the success of CIRC cooperative model application in increasing the quality of students learning process and outcome in reading comprehension of Class VIII students of SMP Purnama 3 Kota Jambi. This research is Classroom Action Research. The location of the research is SMP Purnama 3 Kota Jambi. The total number of the students is 23 students. This research consists of two cycles, in which every cycle uses planning, action, observation, and reflection. The instrument of the research is observation sheets, field note, questionnaire, and test. The technique of analyzing data is by using data reduction, data presenting, and conclusion. While the data of students learning quality is taken from mean formulae. The result of the research is that the application of CIRC cooperative model makes the process of learning becomes interesting, fun, and having contribution because the students show their active response in learning process. The students become autonomous, creative, and aware in thinking and solving problems in reading. In cycle I, the students are in enough criterion (71,5%) and in cycle II it is increasing to good criterion (82%). The mean score of cycle I is 71,25 which falls in enough criterion and the score in cycle II is increasing to 82 which falls to good criterion. Based on the result of the research, it can be concluded that the application of CIRC cooperative model is useful in increasing the quality of learning process and learning outcome of students reading comprehension. The research suggests to those especially to the teacher of Indonesian language and art of Junior High School who happen to have the same problem can apply this model as a reference on the same research. In contrast, the classroom action research by using CIRC cooperative model need a further investigation by using innovative development.Keywords: CIRC Cooperative Model, Learning Quality, Reading Comprehension